Organizational conflict readings in concept in light of the Algerian experience - benkhaled, djamel; benkhaled, elhadj (Journal of Social Sciences and Humanities, 2021)
Conflict within the industrial organization is one of the most important problems facing the economic establishment, as it affects all levels, whether it is between administrators in their own right or between workers with each other, or with workers and administrators (their subordinates), and this phenomenon (conflict) in turn may hinder the process of work from On the one hand, and on the other hand, it may affect the achievement of the goals of this organization, whether in terms of time, effort, or creativity, since the parties to the conflict are engaged in the problems that exist within the organization, neglecting their original work assigned to them, and this leads to default in the work, and imbalance in the institution or even Decrease in production. The phenomenon of conflict may have positive aspects by exploiting the conflict in order to achieve the goals of this organization, in order to aspire to a prosperous future for the institution, its development and promotion in order to achieve its goals and achieve its interests. And it may not be that there was originally a struggle within the industrial organization, because it is a hypothesis that accepts reason and also wrong.